La protección jurídica del medio ambiente en la jurisprudencia de la Corte Interamericana de Derechos Humanos - Valerio de Oliveira Mazzuoli; Gustavo de Faria Moreira Teixeira (Universidad Hemisferios, 2014)
This article examines the interconnections between environmental issues and the protection of human rights, in a process that began in the United Nations Conference on the Human Environment (Stockholm, 1972) and has been developed by the greening of the regional human rights systems. In the Inter-American system the article 11 of the Additional Protocol to the American Convention on Economic, Social and Cultural Rights of 1988 — the Protocol of San Salvador — guarantees the right to a healthy environment. However the American Convention (on its arts. 3-25, 44-51 and 61-69) and its Additional Protocol (on its arts. 8, 13 and 19.6) only allow the submission of individual petitions to the Inter-American Commission and the possible acting of the Inter-American Court, in complaints containing alleged violations of civil and political rights, trade union rights and the right to education. Despite the lack of devices that are capable to ensure an effective protection to the right to a healthy environment, by itself, the Inter-American Court has demonstrated the greening of the human rights, which means, in other words, that it is quite possible to protect environmental issues by the demonstration of its interconnections with civil and political rights that are directly protected by the inter-American system. Therefore, it is necessary to understand the contributions of the jurisprudence of the Inter-American Court in the strengthening of the civil and political rights in cases related to environmental issues.